Management and Employees Perception Analysis on Sugar Industry Waste Management Based on Cleaner Production - Siti Mardiana; Retno Widhiastuti; Luqman Erningpraja (Britain International for Academic Research (BIAR) Publisher, 2020)
The analysis of management’s and employees’ perceptions is needed to create strategies and policies on sugar industry waste management based on cleaner production, to reach the concept of cleaner production by reusing, reducing, and recycling waste. The research’s scope is analyzing management’s and employees’ perceptions toward cleaner production principles, that includes Good Housekeeping knowledge aspects, environmental aspect, social-institutional and economical aspects. The aim of the research is to get strategies and policies on sugar industry waste management based on cleaner production, based on management’s and employees’ perceptions toward the application of waste management based on cleaner production at sugar industry. The research was done in Sei Semayang Sugar Factory, Kwala Sugar Factory, and Tjoekir Sugar Factory. Primary data was tested by Alpha Cronbach and Lickert ordinal scale transformed into interval scale using Successive Interval method. To understand the connectivity between variables, multiple linear regression analysis was used, using SPSS 11.5, and then descriptively analyzed. Analyzing Sei Semayang Sugar Factory’s management’s and employees’ perception toward cleaner production results in the knowledge that technical aspect is an influential aspect in factory’s efficiency and waste management. Kwala Madu Sugar Factory management’s and employees’ perception is that environmental aspect, Good Housekeeping aspect, technical aspect, and knowledge aspect, are influential toward sugar industry waste management. While Tjoekir sugar factory management’s and employees’ perception is that social institutional and economical aspect is the influential aspect toward sugar industry waste management. Sugar industry waste management based on cleaner production strategy based on management’s and employees’ perception is an integration between technical aspect, environmental aspect, Good Housekeeping aspect, and social institutional and economical aspect.